Hakikat Keilmuan Hukum Sistem Civil Law dalam Perspektif Teori Hukum Murni - Nabillah, Tahsya; Prasetiyo, Rio Wibowo Agung; Ohoiwutun, Y.A Triana; Rato, Dominikus (Universitas Muhammadiyah Kotabumi, 2025)
In the development of modern legal science, understanding the essence of legal science has become increasingly important in explaining the position of law as an autonomous discipline amid social, moral, and political influences. This study aims to examine the essence of legal science based on Hans Kelsen's pure theory of law and its relevance to the development of legal science in civil law and common law systems. The research method used is normative jurisprudence with three approaches, namely the legislative approach to examine the hierarchy of norms in the legal system, the conceptual approach to examine the Grundnorm and Stufenbau des Recht theories, and the comparative approach to compare the application of these theories in the two legal traditions. The results of the study show that Kelsen's concept of the hierarchy of norms is in line with the codification system in civil law, because each norm derives its validity from a higher norm, culminating in the basic norm. Meanwhile, in common law, Kelsen's thinking remains relevant because judicial decisions can be understood as legal norms that are valid and binding within the hierarchy of norms. Thus, Hans Kelsen's Pure Theory of Law provides a universal conceptual foundation for the development of legal science as a rational, systematic, and autonomous discipline.